Obesity And The Spleen - Sanjay Kalra; Suneet Kumar Vermaz; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
This review describes the relationship of splenomegaly, or “splenic obesity”, with metabolic syndrome, obesity and metabolic – associated steatohepatic disease (MAFLD), based on animal and human studies. The spleen is enlarged in obesity. It may play a protective role against obesity-associated inflammation and complications. This protection may be lost after splenomegaly. Persons with splenic disease must be evaluated for obesity, and vice versa and counselled to avoid injury to the organ. Keywords: MASLD, NAFLD, obesity, overweight, portal hypertension, spleen, splenectomy, weight